EFFECT OF ANTISTRESS AGENTS ON THE PERFORMANCE OF BROILER UNDER DIFFERENT MANAGEMENT SYSTEMS (Indian Journal of Animal Production and Management, 2015)
A study was conducted to investigate the effect of different anti-stress agents on the growth performance and survivability of broilers. Four hundred and eight day old chicks were randomly divided into two groups and reared under cage and deep litter system respectively. Each group was further divided into 4 sub-groups of 51 chicks each and were given different anti-stress agents along with standard broiler ration. Group T 1 & T 5 were treated as Control, Group T 2 & T 6 were treated with Zeetress , Group T 3 & T 7 were treated with Glucose and Group T 4 & T 8 were treated with honey under cage and deep litter system respectively. The body weight gain and Feed Conversion. Ratio was significantly (P
Keywords: Commercial broilers; Cage system; Deep litter system; Anti-stress agent